RECOGNITION OF CORONA DISCHARGE PRESENCE BY ACOUSTIC SYSTEM INSTALLED ON UNMANNED AERIAL VEHICLE - Gryb, Oleh; Karpaliuk, Ihor; Shvets, Serhiy; Zaporozhets, Artur (Proceedings of National Aviation University (archive), 2020)
The energy complex of Ukraine still remains a rather powerful complex among the countries of the Eurozone. Ukrainian electrical networks, which are part of the energy complex, have significant branches. The length of high and ultra-high voltage power lines (750, 330, 220, 110 kV) is thousands of kilometers. Deterioration of equipment in the power supply system of Ukraine affects the reliability of power supply and quality indicators. In such conditions, maintenance of the operating condition of the equipment is provided by routine maintenance. Considerable attention is paid to the timely detection of damage, accurate determination of the accident site and its nature. High voltage in the network leads to the appearance of such a side factor as corona discharge, which not only consumes significant amounts of electrical energy, but also distorts it. The appearance of a corona discharge may indicate an electrical malfunction of the current transmission system. Therefore, the authors chose the direction of developing galvanically independent systems for diagnosing the state of power equipment through diagnosing the presence of a corona discharge. For determining the presence of a corona discharge, it is necessary to use either a significant number of diagnostic systems, or the location of such systems on mobile platforms. It is proposed to use unmanned aerial vehicles as a platform. The methods of acoustic control proposed by the authors can be blocked by the intrinsic noises of aircraft. Therefore, an acoustic analysis of various operating modes of aircraft was carried out and compared with the acoustic spectrum of a corona discharge. The obtained results made it possible to visualize the possibility of using acoustic systems on board unmanned aerial vehicles to diagnose corona discharge by acoustic parameters.